Comparative Effects of Daily Adjustable Progressive Resistance Exercises Technique & Close Kinetic Chain Exercises on Extensor Lag in Post-Operative Knee Stiffness - Shanza Tanveer, Rabiya Noor, Hamna Afzal, Misdaaq Batool, Kiran Iqbal, Sarah Sabir, Waqas Latif, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Post-operative knee stiffness is caused by arthrofibrosis and functional limitation. Extensor lag is commonly prevalent after knee surgery. There are different approaches to treat this condition. Close kinetic chain exercises are hypothesized as one of effective treatment. DAPRE technique has remarked effects. Aim: To determine effects of DAPRE technique and close kinetic chain exercises on pain intensity, ROM, function, strength among post-operative knee stiffness. Study Design: Randomized control trial. Methodology: Total of 22 patients with post-operative knee stiffness were recruited and divided in two groups. One group received DAPRE technique and other group received close kinetic chain exercises were participated by using a Non-probability convenience sampling technique. Results: The result showed statistically significant difference in both groups in terms of NPRS, WOMAC index, ROM and strength with P-value less than 0.05. Conclusion: It was concluded that Close kinetic chain exercises was more effective than the Daily adjustable progressive resistance exercises on extensor lag for post-operative knee joint stiffness to improving the pain, physical function, range of motion and strength.